The effectiveness of the unity campaign advertisement among university students in Malaysia / Soraya Zahra Mohd Zaki Mubarak - Mohd Zaki Mubarak, Soraya Zahra (2023)
The lack of unity among youth in Malaysia and its causes and consequences. The study is motivated by the observation that the ethnic relations among the youth in Malaysia are only at the average level, despite the government’s efforts to promote national unity and social cohesion through various policies and campaigns. This study seeks to investigate the impact of unity campaign advertisements on university students at UiTM Alor Gajah, Malaysia. This research seeks to assess the efficacy of advertisements that aim to raise awareness, understanding, and acceptance of national unity principles among these demographics. An applied quantitative methodology is taken to explore the dynamics between unity campaign ads and student perception, specifically how various aspects of these advertisements influence support or opposition for My Generasi concept. This study explores how an advertisement impacts various demographic subgroups, such as gender, ethnicity, and academic discipline. These findings aim to offer policymakers, educators, and media practitioners’ concrete suggestions for designing and implementing more successful campaigns. Although this study has some inherent restrictions, such as its narrow focus on one university and inability to capture in-depth qualitative insights or changes over time, it provides important insights into how advertising helps promote national unity among Malaysian youth.